Increasing the Efficiency of Solar Electric Power Utilization - V. A. Pobedushkina (Мир новой экономики)
The relevance of the study is driven by the rapid development of solar energy and the search for opportunities to increase its efficiency in order to ensure a more stable energy supply for the population and improve the quality of life.The objective: to identify the key features of the global experience in using solar trackers for power generation.Research methods: mathematical analysis, empirical data analysis, systematization, investment analysis.Findings: this study examines various types of solar panels and their impact on the economic efficiency of solar energy projects. A review of relevant literature and scientific-practical studies confirms the versatility of solar trackers in different geographical and climatic zones. The study includes calculations of key investment attractiveness indicators for projects utilizing solar trackers and stationary systems, demonstrating the low efficiency of the latter. Key directions for the development of this technology have been identified, and recommendations for its improvement are provided.Practical significance: the main conclusion of this study may be useful for justifying the feasibility of using trackers at solar power plants and for exploring ways to improve the efficiency of solar generation.